D-Shape Asymmetric Excision of Sacrococcygeal Pilonidal Sinus With Primary Closure, Suction Drain, and Subcuticular Skin Closure: An Analysis of Risks Factors for Long-Term Recurrence. (April 2015) - Brusciano, Luigi; Limongelli, Paolo; del Genio, Gianmattia; Tolone, Salvatore; Amoroso, Vincenzo; Docimo, Giovanni; Docimo, Ludovico
Background . Few studies have reported long-term recurrence rates after asymmetric excision with primary closure in the treatment of sacrococcygeal pilonidal disease. Methods . A retrospective analysis of a prospectively maintained database of 550 surgical excisions performed for sacrococcygeal pilonidal disease between 1988 and 2005 was performed. Results . A total of 550 patients with a diagnosis of pilonidal sinus underwent surgical excision over a period of 17 years. Thirty-eight out of the 550 patients (3.5%) were lost at follow-up. At a mean follow up of 11.2 ± 5.3 years, median 11 years (range = 3-22), the recurrence rate was 8.9%. Actuarial 1-, 5-, 10-, and 20-year disease-free survival rates were 98%, 94%, 92%, and 83%, respectively, with a median overall disease-free survival of 10 years (95% confidence interval [CI] = 3-15). When patients were stratified according to several variables known to influence recurrence, an age of less or ≥22 years (odds ratio [OR] = 1.5, 95% CI = 0.3-7.5, P = .001), a family history of sinus (OR = 5.9, 95% CI = 2.7-12, P = .0001), and intraoperative methylene blue use (OR = 6.3, 95% CI = 1.2-31, P = .024) were indicated as independent predictors of disease-free survival rates. Conclusions . D-shape asymmetric excision and scar lateralization, with primary multilayer subcuticular closure, suction drain insertion, and skin closure in patients with sacrococcygeal pilonidal disease is a safe and adequate surgical treatment offering an effective healing rate as well as low recurrence. Several features are likely to predict a better or a worse long-term recurrence rate in patients undergoing surgery for sinus pilonidalis.